Performance Efficiencies of Domestic and Foreign Islamic Banks in Malaysia - Rossazana, Ab. Rahim; Norlina, Kadri; Farhana, Ismail (Institute of Bankers Malaysia, 2013)
This study examines the performance efficiencies of full-fledged Islamic banks in Malaysia for the period from 2006 to 2011. The Malaysian Islamic banking industry has grown tremendously in terms of assets, deposits and total financing over the study period. Data Envelopment Analysis (DEA) is employed in this study to measure the cost efficiency as well as the technical efficiency and its decompositions. The results show that, on average the main contributor of cost efficiency for Islamic domestic and foreign banks in Malaysia is allocative efficiency. In addition, the results find that foreign Islamic banks are more efficient than domestic banks with respect to pure technical efficiency and allocative efficiency.